Penyaluran Dana Zakat Untuk Pendidikan Dalam Program Sumsel Cerdas Di Badan Amil Zakat Nasional (Baznas) Provinsi Sumatera Selatan Menurut Ekonomi Islam - Oki Sapitri Menghayati (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2022)
The aims of this study were: (1) to determine the implementation of the distribution of zakat funds for education in the Smart Sumsel Program at the National Amil Zakat Agency (BAZNAS) of South Sumatra Province, (2) to determine the impact of distributing zakat funds to the education costs of the underprivileged, and (3 ) to find out the view of Islamic economics on the distribution of zakat funds for education in the Smart Sumsel Program at the National Amil Zakat Agency (BAZNAS) of South Sumatra Province. Field research is research conducted in the field. The author conducted this study to obtain data that was used as a primary source, then to support this research also used secondary data taken from books and other sources related to the Islamic economics review on the distribution of zakat funds to the National Amil Zakat Agency (BAZNAS) in Smart Sumsel Program. The data collection techniques used include observation, interviews and documentation, while the descriptive qualitative data analysis technique is analyzing the data obtained in the field with theoretical results on the problem of zakat based on observations, interviews and documentation, it will be described as clearly as possible and then collected. BAZNAS Sumsel gives zakat to the Smart Sumsel Program to finance the poor to get education, build schools and fulfill their operational needs in order to stem and fight the hegemony of capitalist, communist, secular education and so on towards pure Islamic education. The children who will be financed are children who have met the requirements and procedures by the South Sumatra BAZNAS, such as memorizing the Qur'an. the percentage of fund allocation for foster children is distributed equally with other BAZNAS programs, such as sumsel prospering, sumsel taqwa, sumsel care and development.